In vitro interactions of CysB protein with the cysK and cysJIH promoter regions of Salmonella typhimurium. - Monroe, R S (1990)
The cysteine regulons of Salmonella typhimurium and Escherichia coli are positively regulated by CysB protein and either O-acetyl-L-serine or N-acetyl-L-serine, both of which act as inducers. Gel mobility shift assays and DNase I footprinting experiments showed that CysB protein binds to the S. typhimurium cysK promoter at two sites, one, designated CBS-K1, at positions -78 to -39 relative to the major transcription start site, and the other, designated CBS-K2, at positions -115 to -79. The S. typhimurium cysJIH promoter was found to contain a single binding site, designated CBS-JH, at positions -76 to -35. Acetyl-L-serine stimulated binding to CBS-K1 and CBS-J and inhibited binding to CBS-K2. In the absence of acetyl-L-serine, CysB protein bound to both CBS-K1 and CBS-K2 and gave a complex that migrated more slowly during gel electrophoresis than did that formed in the presence of acetyl-L-serine, in which case CysB protein bound only to CBS-K1. Complexes formed with DNA containing the two binding sites either at the middle or at one end of the fragment migrated differently, suggesting that DNA was bent in the slow complex formed in the absence of acetyl-L-serine and that DNA in the fast complex was less bent or not bent at all. An analysis of upstream deletions of the cysK promoter showed that only CBS-K1 is required for in vivo promoter activity. CBS-J is analogous in position to CBS-K1 and is probably also required for activity of the cysJIH promoter. CBS-K2 has no known function but may help sequester CysB protein at the cysK promoter.